Directed Study of Abietic Acid Reaction in Pine Rosin under Non-Precious-Metal Catalyst - Siti Nurul Afifah; Masruri Masruri; Arie Srihardyastutie; Moh. Farid Rahman (Syarif Hidayatullah State Islamic University, 2022)
Pine rosin of Pinus merkusii Jung at de Vriese is produced industrially from a distillation process of pine sap. The high total Indonesian production leads the primary derivatization strategy into several derivates to fulfill the market demand. Abietic acid (AA) is a major compound in pine rosin, used as the object of observation in this study. The general methodology for transformation reported involves using palladium (Pd) and platinum (Pt)-based catalysts. Both are precious metal catalysts to proceed with oxidative dehydrogenative-aromatization of the rosin. The synthesized product provides dehydroabietic acid (DHA) derivatives in high yield. This paper reports that non-precious metal-based catalysts such as iron (Fe), zinc (Zn), or copper (Cu) with iodine (I2) were applied to deliver the reaction by steam cracking without nitrogen (N2) and oxygen (O2) for economical, efficient, and greenway’s catalyst. It was found that a similar product was isolated, including several by-products. Under high temperatures with a various metal transitions and halogen by FeCl3-I2 and Cu(NO3)2.3H2O and ZnCl2 catalyst, four compounds were identified employing spectroscopic methods in the reaction product: 7-hydroxy-dehydroabietic acid (5), 1,7-dihydroxy-dehydroabietic acid (6), 7-isopropyl-1-methylphenanthren-9-ol (7) and polymer (8). This modified pine rosin was mainly used as an emulsifier for the synthetic rubber industry, varnish, ink, paper sizing, etc. The products are determined based on LC-MS/MS, UV-Vis, and ATR-FTIR spectroscopy.